Marketing Relations Performance Behavior in Value Chain Based Credit Initiative - Utomo, Bagus Satrio; Widoningrum, Luluk Nastiti; Raharjo, Susilo Toto; Sukresna, I Made (LifeSciFi, 2025)
Value Chain Financing (VCF) is a financing approach that leverages financial instruments, practices, and technology to optimize the management of working capital and liquidity throughout the value chain process, involving the parent company, supplier companies, distributors, or agents as end users. By effectively utilizing data, Bank BRI can enhance its financial performance, strengthen its competitive position, and deliver added value to customers. For the marketing staff at Bank BRI in the Jakarta 2 Regional Office, particularly in the context of the retail loan business, this database plays a pivotal role in formulating strategies to improve performance in credit initiatives based on the Value Chain database. In the retail loan sector at Bank BRI, the value chain database significantly contributes to improving efficiency, effectiveness, and service quality. This study adopts a qualitative approach to explore and gain insights into the marketing performance behavior at the Jakarta 2 Regional Office, specifically in relation to the execution of value chain-based credit initiatives. The aim of this research is to examine how the Value Chain Database can enhance the performance of the marketing staff at Bank BRI in the Jakarta 2 Regional Office, enabling them to devise strategies that improve marketing outcomes, supported by value chain-based credit initiatives.